A cost-effective fluorescence detection system for pulsed laser analysis. (February 2015) - Kerns, P.M.; Lafferty, J.W.; Fox, N.A.; Basu, S.
Abstract: A cost-effective fluorescence detection system has been developed using a National Instruments PCI-6251 data acquisition (DAQ) board that is driven by LabVIEW Signal Express. The signal is collected using a collimator and transported to the DAQ board using a fiber-coupled detector. The same detection system has been incorporated into an inverted microscope fitted with internal dichroic mirrors to provide a cost-effective alternative to commercial fluorescence microscopes. The detection system has been used to measure fluorescence intensity and generate a laser power curve that can be used for pulsed lasers. Different data analysis approaches have been compared and standard deviation and signal-to-noise ratios have been determined.